A half-century of studies on a chromosomal hybrid zone of the house mouse - Giménez, Mabel Dionisia (2016)
The first natural chromosomal variation in the house mouse was described nearly 50 years ago in Val Poschiavo on the Swiss side of the Swiss–Italian border in the Central Eastern Alps. Studies have extended into neighboring Valtellina, and the house mice of the Poschiavo-Valtellina area have been subject to detailed analysis, reviewed here. The maximum extent of this area is 70 km, yet it has 4 metacentric races and the standard 40-chromosome telocentric race distributed in a patchwork fashion. The metacentric races are characterized by highly reduced diploid numbers (2n = 22–26) resulting from Robertsonian fusions, perhaps modified by whole-arm reciprocal translocations. The races hybridize and the whole Poschiavo-Valtellina area can be considered a “hybrid zone.” The studies of this area have provided insights into origin of races within hybrid zones, gene flow within hybrid zones and the possibility of speciation in hybrid zones. This provides a case study of how chromosomal rearrangements may impact the genetic structure of populations and their diversification.